UNIVERSITY STUDIES ( 1736 – 1740 ) OF KRISTIJONAS DONELAITIS IN THE LIGHT OF SERIES PRAELECTIONUM - NARBUTIENĖ, DAIVA (Knygotyra, 2015)
The aim of this article is to analyze a significant source on Donelaitis’ years of study at the University of Konigsberg – a unique bound set of university term lecture lists kept in the National Library of Poland in Warsaw (BN – XVIII.3.11061–XVIII.3.11090). This is a bound set of documents in Latin that consists of 31 notebooks: 31 lists of instructors and their lectures encompassing the period of 1720–1740. Here it is called Series praelectionum (i. e. lecture lists) based on its main keywords. In German historiography these lists are known as Vorlesungsverzeichnisse der Universitat Konigsberg, while the Italian culture historian Riccardo Pozzo has compiled and published a lecture catalogue of the University of Konigsberg for 1719–1804 with the Latin title: Catalogus Praelectionum Academiae Regiomontanae. The present author discusses a provenance of this source, concluding that this unique bound set, like numerous other rare publications from the “Academia Regiomontana” collection, came to the National Library of Poland from the Konigsberg city library after the end of World War II in 1945. Donelaitis started his studies at the University of Konigsberg in the winter term of 1736 and completed them in the spring of 1740. The lists of lectures and instructors for this period constitute a part of the bound set: eight notebooks out of 31. The term lists provide much interesting information on the specifics of university life and individuals whose lectures Donelaitis attended. Apart from his studies at the Faculty of Theology and a seminar on the Lithuanian language, Donelaitis might have attended lectures delivered by other instructors, presumably from the Faculty of Philosophy. It is well known that after his graduation Donelaitis was well versed not only in theology, but also poetics, literature, natural sciences, musical theory and practice. In acquiring all these skills and knowledge he was probably helped by instructors from the Faculties of Law, Medicine and Philosophy, whose names and lecture courses also are on the same lecture lists, a source providing information on lesser known areas of Donelaitis’ encyclopedic education.